Endothermy in Birds and Mammals: How the Relationships between Body Weight and Metabolic Rate, Body Temperature, Sleep and Activity Duration Developed in the History of Formation of Endothermic Vertebrates - Gavrilov, Valery M. (Innovations in Biological Science Vol. 4, 2024)
Here we present a meta-analysis of literature sources and original data on basal metabolic rates (BMR) in birds and mammals based on 1817 measurements (817 data points from mammals and 1000 from birds). We used these data to estimate scaling coefficients and intercept for all endothermic animals pooled and for birds and mammals separately to study the difference between these classes, and also for the main groups of lower taxonomic status. We considered BMR variation and the duration of activity in three mammalian subclasses: monotremes, marsupials and eutherians, and in three groups of birds: palaeognaths, neognaths non-passerine and passerines, depending on the evolutionary age of these groups. In all groups BMR varies with body size with the different scaling coefficient which is statistically indistinguishable from ¾ in mammals and 2/3 un birds, but with significantly different intercepts. The data for all the considered groups were combined and the common exponent for six allometric equations between the BMR and body weight was established b = 0.7248. Reduced to the common slope, the relative metabolic rate forms the following series: Neognathae - Passeriformes - 1.00, Neognathae - Non-Passeriformes - 0.75, Palaeognathae - 0.53, Eutheria - 0.57, Marsupialia - 0.44, and Monotremata - 0.26. The main finding is that the metabolic rate in the six main groups of mammals and birds consistently increases as the geological time of the group’s divergence approaches the present. Activity duration varies between the main groups of endotherms. Overall sleep duration is a parameter inversely related to the overall activity. A high level of activity is related to high BMR. Placentals and paleognaths have similar BMR, i.e. terrestrial lifestyle without flight is based on nearly equal BMR. We calculated sleep duration in the main groups of endotherms on the basis of literature data. BMR in a taxon correlates with its evolutionary age: the later a clade diverged, the higher is its metabolic rate and the longer is activity period. BMR of eutherians and flightless paleognaths is similar, and these groups evolved at practically the same time. We suggest that each group formed its taxon-specific BMR depending on the ability to maintain thermal homeostasis under the environmental conditions that prevailed during its emergence. Monotremes were the first to branch off from the basal mammals and have the lowest BMR among the endotherms we consider. This level is minimally sufficient for maintaining homeostatic body temperature under a very limited range of environmental conditions. The next level is typical of marsupials and allows them to maintain thermal homeostasis under a broader range of conditions and have a more protracted period of activity. Finally, the metabolic rate typical of placentals and paleognaths formed in the mid-Cretaceous and allowed these groups to occupy a broader range of terrestrial niches. Immediately when the development of blood circulation and respiratory systems made it possible to reach the BMR that allowed maintaining a body temperature of 37 oC, the explosive radiation of mammals and birds started. In the mid and late Cretaceous birds and mammals started to occupy the leading positions in the ecosystems. And at last, some 50 mya passerines that have the highest BMR (nearly 50% higher than eutherians and paleognath birds) adapted to the forest habitats and gained body temperature of ca. 40oC, which is at the upper physiological limit. The duration of activity and body temperature increased in parallel to the BMR. Ecological expansion of birds and mammals resulted in their worldwide geographic distribution. A relatively similar energetic analogue of passerines in mammals are humans, who have BMR ca. 35% higher than predicted by the scaling equation for mammals, have amazing reproductive potential, large brains and longevity much exceeding the live duration which is typical for their body-mass specific mean. Sleep duration in humans is 30% shorter than the mammals-specific mean, and it is one of the evolutionary youngest species. At the moment the global population of humans exceeds 8 billion people.